Dynamic Analysis of Railway Vehicle–Track Interaction: Modeling Elastic–Viscous Track Properties and Experimental Validation - Vladimir Gelevich Solonenko; Janat Sultanbekovich Musayev; Narzankul Musayevna Makhmetova; Arman Aydinuly Malik; Gulnaz Tleubaevna Yermoldina; Semyat Turganzhanovich Akhatov; Nataliya Viktorovna Ivanovtseva (Applied Sciences, 2025)
This study investigates the dynamic interaction between railway vehicles and tracks, focusing on the effects of elastic–viscous properties of spring suspensions and track inertia. This research examines vertical oscillations of a railway car moving on a non-uniformly elastic track, modeled as a system with lumped parameters. Analytical and numerical methods are employed to derive track parameters by comparing frequency characteristics of continuous and discrete models. Key findings reveal that adjacent wheelsets influence interaction forces and bending moments by approximately 10%, while rail deflections are affected by up to 20% within the speed range of 60–180 km/h and for disturbances up to 20 Hz. Experimental validation using a roller test rig confirms the theoretical predictions, demonstrating the significance of track inertia and damping in dynamic analyses. This study provides practical recommendations for improving railway vehicle design and track maintenance, emphasizing the need to account for nonlinearities and inertial effects in high-speed scenarios.